Beyond the inclusion-exclusion binary: right mindfulness and its implications for perceived inclusion and exclusion in the workplace - Vu, Mai Chi (Journal of business ethics, 2024)
This study examines non-Western perceptions of inclusion and exclusion through an examination of right mindfulness practitioners in Vietnam. It contributes to the critical inclusion literature that problematizes inclusion by showing how right mindfulness practitioners rejected the concepts of inclusion and exclusion, and moreover, resisted attachments to feelings of inclusion or exclusion, treating both states as empty and non-enduring. Surprisingly, our study shows how inclusion can generate fear at fulfilling others' collective expectations, whereas exclusion generated a sense of freedom arising from a release from those expectations. Further, our study traces these counter-intuitive findings to right mindfulness practitioners' moral reasoning based upon Buddhism's canonical philosophical ideas. We conclude by highlighting the pressing need for critical perspectives and for further non-Western perspectives to inclusion that contribute to a body of cross-cultural work.